(untitled) (Acta Scientiarum. Agronomy, 2025)
The mechanisms underlying the interactions between native mycorrhizal fungal communities and strawberry plants remain unclear. However, the identification of specific associations among variables and their influence on the total experimental variability when using inoculants based on arbuscular mycorrhizal fungi should enable the identification of the most relevant ones. Herein, our objective was to identify and characterize variables related to each other and to the total experimental variability among strawberry plants inoculated with native mycorrhizal communities. Experimental treatments included an uninoculated control and eight multi-specific inoculants from cultivated soils and native forests from reference strawberry-cultivation sites (Bom Princípio, Flores da Cunha, Ipê, and São José of Hortêncio) in Rio Grande do Sul State, Brazil. Morphological, productivity, and quality traits were evaluated. Inoculants obtained from agricultural ecosystems of Bom Princípio and Ipê did not influence the horticultural performance of strawberries, while those from Flores da Cunha largely explained total experimental variability, and therefore, should be considered when selecting the location to obtain inoculants for use on strawberry plants. Number of fruits, fruit flavor, chlorophyll a, and total chlorophyll contents, and, most importantly, root variables, should be included for experimental analysis of ‘Albion’ strawberry responses to multi-specific mycorrhizal inoculants from different locations.